Assessing the reliability of serum macrophage migration inhibitory factor as a marker for diabetic nephropathy prediction in type 2 diabetes patients and the effect of ACE inhibitors on its level - Sumaya B. Abdulrahman; Eman S. Saleh; Sabah M. Saeedi (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract Diabetic nephropathy (DN) is a prevalent chronic microvascular diabetic complication. As inflammation plays a vital role in the development and progress of DN the macrophages migration inhibitory factor (MIF), a proinflammatory multifunctional cytokine approved to play a critical function in inflammatory responses in various pathologic situations like DN. This study aimed To assess serum levels of MIF in a sample of Iraqi diabetic patients with nephropathy supporting its validity as a marker for predicting nephropathy in T2DM patients. In addition, to evaluate the nephroprotective effect of angiotensin-converting enzyme (ACE) inhibitors in terms of their influence on MIF levels. This is a case-control study involving ninety subjects that have been divided into three groups: twenty apparently healthy control group and seventy patients with type 2 diabetes mellitus divided into two equal groups according to the presence of diabetic nephropathy that has been further divided into two groups according to the use of ACE inhibitors or not. Serum MIF, urea, creatinine, RBS, HbA1c, BMI, eGFR, and urinary albumin to creatinine ratio have been measured for each subject. Serum MIF’s highest levels were observed in the diabetic nephropathy patients (24.9 ng/ml) followed by the diabetics (14. 1 ng/ml) with the lowest level observed in the control group (4.8 ng/ml). There was a significant relation between MIF levels and ACE inhibitors (p-value <0.05) with reduced MIF levels in ACE inhibitors users. The ROC curve showed that MIF has a good performance in disease prediction. These findings support the reliability of MIF as a biomarker for the prediction of diabetic nephropathy and the possible reducing effect of ACE inhibitors on MIF levels.